2018
DOI: 10.1177/2045125318759461
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric manifestations in Wilson’s disease: possibilities and difficulties for treatment

Abstract: Wilson’s disease (WD) is an inherited metabolic disorder related to disturbances of copper metabolism, and predominantly presents with liver and neuropsychiatric symptoms. In most cases it can be successfully treated with anti-copper agents, and both liver function and neuropsychiatric symptoms typically improve. Treatment guidelines for WD include recommendations for anti-copper treatment as well as for the treatment of liver failure symptoms. Recently, recommendations for treatment of the neurological sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
89
0
22

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 85 publications
(212 reference statements)
1
89
0
22
Order By: Relevance
“…In previous studies, a variety of psychiatric symptoms have been reported in WD, including emotional lability, mood disorders, and behavioral and personality changes. The amygdala and hippocampus play important roles in emotional processes, learning, and memory.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In previous studies, a variety of psychiatric symptoms have been reported in WD, including emotional lability, mood disorders, and behavioral and personality changes. The amygdala and hippocampus play important roles in emotional processes, learning, and memory.…”
Section: Discussionmentioning
confidence: 97%
“…Wilson's disease (WD) is a progressive autosomal‐recessive genetic disorder of copper metabolism, with principally hepatic, neurological, and psychiatric manifestations. The neurological symptoms of WD develop in almost 40% to 50% of patients and are characterized by involuntary movements, speech disturbances, dysphagia, autonomic dysfunction, and gait and balance disturbances . Up to 30% of WD patients have manifested with psychiatric symptoms at the time of diagnosis .…”
mentioning
confidence: 99%
“…These symptoms may precede the hepatic and neurological symptomatology by a significant period of time. Other psychiatric manifestations include personality changes (antisocial behavior, irritability, and disinhibition), mood disorders (bipolar disorders, manic and hypomanic syndrome, depression, suicidal attempts), psychosis, anorexia, dyssomnias, sexual dysfunction, and cognitive impairment (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…Psychiatric problems may not be recognised as a symptom of WD. They are common in adults with a quarter having symptoms at presentation and almost all developing symptoms over the course of the disease 19–21…”
Section: Neuropsychiatric Manifestationsmentioning
confidence: 99%